Degradation Characteristics and Mechanism of Black Sandy Dolomite with Fluid Added in a Mechanical Test - Xin Liao; Qi Xu; Sixiang Ling; Angran Tian; Qiang Tang (Geofluids)
Sandy dolomite, being a soluble rock, is prone to dissolution and erosion caused by groundwater, leading to the formation of underground caves and fractures. This may result in geological disasters such as ground subsidence and collapse. In this paper, the changes and mechanical properties of black sandy dolomite after hydrochemistry are studied. A semi-immersion test with different concentrations of iron sulfate solution was carried out to simulate the water-rock interaction in different water environments. After that, scanning electron microscope (SEM) results could reflect the dissolution and pore development of rock by the effect of water-rock interaction from the microscopic. Water-rock interaction enlarges cracks in rocks and dissolves pyrite, carbonate minerals, and other components, reducing the cementation between particles. The change in the mechanical properties of black sandy dolomite under water-rock chemical interaction was revealed by uniaxial compression test. The mechanical properties of the samples exhibit varying degrees of deterioration, with strain increased ranging from 4.96 to 29.58%. The brittleness index modified (BIM) values for each sample ranged from 5.20 to 6.20%, all of which are larger than 4.70% in the natural state.